Corrosion prevention of hot-dip galvanized wire and process thereof

CN122979800APending Publication Date: 2026-10-27XINJI AOSEN METAL PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611086073.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]目前工业上普遍采用六价铬钝化工艺,然而六价铬具有较高毒性,废液处理难度大、污染风险高,已受到国内外环保法规严格限制,其应用场景持续收缩

Benefits of technology

1、本申请采用功能颗粒提高镀层致密度与耐磨性,为钝化处理提供平整、稳定的基底,确保功能溶液能均匀成膜、紧密结合;功能溶液通过形成致密钝化膜与缓蚀离子储库,弥补了镀锌层表面存在的微小缺陷,同时增强镀层表面的化学防护能力,抑制镀锌层的氧化腐蚀;功能溶液的无铬钝化体系与功能颗粒改性的镀锌层形成高效协同,进一步放大防护效果,实现了环保性与腐蚀防护的多维度强化。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the field of metal corrosion prevention, and particularly discloses a hot galvanized wire corrosion prevention method and process. The hot galvanized wire corrosion prevention method comprises the following steps: immersing metal wires into a zinc plating corrosion prevention solution, performing zinc plating treatment at 550-560 DEG C, cooling to 80-100 DEG C, washing, drying, and preparing pretreated zinc wires; immersing the pretreated zinc wires into a functional solution, soaking for 3-5 min, drying, and cooling; and the preparation method of the zinc plating corrosion prevention solution comprises the following steps: heating zinc and aluminum to 590-600 DEG C, adding silicon, heat-insulating stirring for 15-20 min, adding functional particles, and continuously stirring for 10-20 min to prepare the zinc plating corrosion prevention solution. The hot galvanized wire corrosion prevention process has excellent environmental protection and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of metal corrosion protection, and more specifically, it relates to a hot-dip galvanized wire corrosion protection method and process thereof. Background Technology

[0002] Hot-dip galvanizing, as an important method of metal surface corrosion protection, widely involves immersing steel in molten zinc to form a zinc and zinc-iron alloy layer on the substrate surface. The corrosion protection effect is achieved through the sacrificial anode protection of zinc. To further enhance the corrosion resistance of the zinc layer and inhibit the formation of white rust, the hot-dip galvanized layer usually undergoes passivation treatment. This process forms a dense and stable passivation film on the surface, transforming the coating from an active state to a passive state, thereby significantly reducing the corrosion rate.

[0003] Currently, hexavalent chromium passivation is widely used in industry. However, hexavalent chromium is highly toxic, and its wastewater treatment is difficult and poses a high pollution risk, which has led to strict restrictions from domestic and international environmental regulations, resulting in a continuous shrinking of its application scenarios. Traditional chromium-free passivation systems generally suffer from insufficient corrosion resistance and poor adhesion to the zinc plating layer, making it difficult to simultaneously meet the requirements of environmental protection and corrosion resistance.

[0004] Therefore, there is an urgent need for an environmentally friendly anti-corrosion liquid suitable for hot-dip galvanized wire that can simultaneously achieve good galvanizing protection and chromium-free passivation, effectively balancing environmental friendliness and corrosion resistance. Summary of the Invention

[0005] In order to achieve both environmental friendliness and corrosion resistance in hot-dip galvanized wire anti-corrosion solution, this application provides a hot-dip galvanized wire anti-corrosion solution and its preparation method.

[0006] Firstly, the hot-dip galvanized wire corrosion protection provided in this application adopts the following technical solution: A process for corrosion protection of hot-dip galvanized wire includes the following steps: (1) Immerse the metal wire in the zinc anti-corrosion solution, galvanize it at 550-560℃, cool it to 80-100℃, wash and dry it to obtain pretreated zinc wire; (2) Immerse the pretreated zinc wire in the functional solution for 3-5 minutes, dry, and cool. The preparation method of the zinc plating anti-corrosion solution includes the following steps: Zinc and aluminum are heated to 590-600℃, silicon is added, and the mixture is kept warm and stirred for 15-20 minutes. Functional particles are then added, and the mixture is stirred for another 10-20 minutes to obtain a zinc-plating anti-corrosion solution.

[0007] Optionally, the mass ratio of zinc, aluminum, silicon and functional particles is 55-60:30-35:0.8-1:0.3-0.5.

[0008] By adopting the above technical solutions, functional particles improve the density and wear resistance of the coating, providing a smooth and stable substrate for subsequent passivation treatment, ensuring that the functional solution can form a uniform film and bond tightly. The functional solution, by forming a dense passivation film and corrosion-inhibiting ion reservoir, compensates for the minor defects on the surface of the zinc coating, while enhancing the chemical protection capability of the coating surface and inhibiting the oxidation corrosion of the zinc coating. The chromium-free passivation system of the functional solution and the zinc coating modified by functional particles form a highly efficient synergy, further amplifying the protective effect and achieving complementary reinforcement in multiple dimensions such as interface bonding and corrosion protection. Moreover, the chromium-free system increases environmental performance.

[0009] Optionally, the method for preparing the functional particles includes the following steps: Nano zinc oxide, aluminum oxide, talc, and nano silica were added to anhydrous ethanol, ball-milled for 40-60 minutes, and spray-dried to obtain functional particles.

[0010] Optionally, the mass ratio of the nano zinc oxide, alumina, talc and nano silica is 1.2-1.5:0.8-1.0:0.4-0.5:1-1.5.

[0011] Optionally, the functional particles undergo the following pretreatment: Add the functional particles to an ethanol solution containing silica sol, activate for 0.8-1 hour, filter, and dry.

[0012] By employing the above-mentioned technical solution, wet ball milling of nano-zinc oxide, alumina, talc, and nano-silica in anhydrous ethanol medium can achieve thorough refinement and uniform dispersion of each inorganic powder, avoiding particle agglomeration. Simultaneously, nano-silica modifies the inorganic particles through in-situ surface coating, improving surface hydrophobicity and interfacial compatibility. Nano-zinc oxide refines the coating grains, fills micropores, and increases coating density. Alumina improves coating hardness and wear resistance, enhancing physical shielding. Talc, with its layered structure, forms labyrinthine channels within the coating, hindering the penetration of corrosive media. The synergistic effect of these components significantly improves the coating's density, wear resistance, and corrosion resistance without significantly affecting the fluidity of the zinc plating solution.

[0013] Activating functional particles in an ethanol solution containing silica sol introduces silanol groups onto the particle surface, improving its hydrophilicity and reactivity. This enhances the wettability and interfacial bonding between the functional particles and the zinc-aluminum-silicon alloy melt, preventing particle agglomeration, floating, or segregation in the high-temperature zinc melt. Furthermore, the particles bond more firmly to the coating substrate, making them less prone to detachment during subsequent tensile and bending stresses, thus avoiding interfacial defects and ensuring the structural stability and long-term corrosion resistance of the composite zinc coating.

[0014] Optionally, the method for preparing the functional solution includes the following steps: (1) Add sodium citrate and tannic acid to water, stir evenly, and adjust the pH of the solution to 5.5-6.5 to obtain sodium citrate solution; (2) Add phytic acid to sodium citrate solution, stir for 5-10 min, add silane coupling agent, and continue stirring for 15-20 min to obtain a mixture; (3) Add sodium molybdate, sodium tungstate and aminotrimethylphosphonic acid to the mixture, continue stirring for 10-15 minutes, let stand, and obtain the functional solution.

[0015] Optionally, the mass ratio of sodium citrate, tannic acid, phytic acid, sodium molybdate, sodium tungstate, and aminotrimethylphosphonic acid is 100:8-10:4-6:0.3-0.5:1.5-2:1.0-1.5.

[0016] By adopting the above technical solution, the siloxane network formed after the hydrolysis of the silane coupling agent can chemically bond with the hydroxyl groups on the surface of the zinc plating layer. At the same time, the polyhydroxy, carboxyl, and phosphate groups in tannic acid and phytic acid can form a stable chelate structure with zinc ions on the surface of the zinc plating layer, constructing a dual bonding system of organic chelation and inorganic crosslinking. This effectively enhances the interfacial bonding force between the passivation film and the zinc plating layer, avoids defects such as peeling, flaking, and cracking of the film, and ensures that the film is not easily separated from the zinc plating layer during subsequent processing, transportation, and use, significantly improving the bonding strength. In terms of corrosion resistance, tannic acid and phytic acid synergistically form a dense organic chelate framework, which can effectively prevent corrosive media such as water, oxygen, and chloride ions from penetrating to the surface of the galvanized layer, reducing the oxidative corrosion of the galvanized layer. Molybdate and tungstate, as oxidizing corrosion inhibitors, are uniformly dispersed and partially embedded in the film layer, forming a corrosion-inhibiting ion reservoir similar to hexavalent chromium passivation. This not only inhibits the anodic dissolution of the galvanized layer, but also migrates and accumulates in the damaged area when the film layer is scratched or damaged, undergoing redox and chelation reactions with the exposed zinc layer, regenerating the passivation repair layer in situ, and preventing the spread of rust. At the same time, aminotrimethylphosphonic acid and sodium citrate synergistically play a complexing and stabilizing role, which can reduce defects such as pores and pinholes in the film layer. Combined with the organic-inorganic hybrid structure formed by the silane coupling agent, the film layer is further densified, improving the water resistance and salt spray resistance of the film layer, effectively delaying the formation of white rust and red rust in the galvanized layer, and increasing the bonding strength and corrosion resistance between the passivation film and the galvanized layer.

[0017] In summary, this application has the following beneficial effects: 1. This application uses functional particles to improve the density and wear resistance of the coating, providing a flat and stable substrate for passivation treatment, ensuring that the functional solution can form a uniform film and bond tightly; the functional solution compensates for the minor defects on the surface of the zinc coating by forming a dense passivation film and corrosion-inhibiting ion reservoir, while enhancing the chemical protection capability of the coating surface and inhibiting the oxidation corrosion of the zinc coating; the chromium-free passivation system of the functional solution and the zinc coating modified by functional particles form a highly efficient synergy, further amplifying the protective effect and achieving multi-dimensional enhancement of environmental protection and corrosion protection.

[0018] 2. By adopting the above-mentioned technical solution, the components of nano-silica, nano-zinc oxide, alumina and talc work synergistically to significantly improve the density, wear resistance and corrosion resistance of the coating without significantly affecting the fluidity of the zinc plating solution. The functional particles are activated in an ethanol solution containing silica sol, which can improve the hydrophilicity and reactivity of the particle surface and prevent the particles from agglomerating, floating or segregating in the high-temperature zinc liquid. Moreover, the particles are more firmly bonded to the coating substrate and are not easy to fall off during subsequent tensile, bending and other stress processes, thus avoiding the generation of interface defects, thereby ensuring the structural stability and corrosion resistance of the composite zinc plating layer.

[0019] 3. This application utilizes a siloxane network formed by the hydrolysis of a silane coupling agent, which chemically bonds with the hydroxyl groups on the surface of the zinc plating layer. Simultaneously, tannic acid and phytic acid form a stable chelate structure with zinc ions on the zinc plating layer surface, constructing a dual-bonding system of organic chelation and inorganic crosslinking. This significantly improves the bonding strength between the passivation film and the zinc plating layer, while effectively blocking the penetration of corrosive media such as water, oxygen, and chloride ions, reducing the oxidation and corrosion of the zinc plating layer. Molybdate and tungstate loaded in the film layer form a passivation and corrosion-inhibiting ion reservoir, preventing the spread of rust. Aminotrimethylphosphonic acid and sodium citrate synergistically reduce defects such as pores and pinholes in the film layer, further densifying the film layer in conjunction with the dual-bonding system of organic chelation and inorganic crosslinking, improving the film layer's water resistance, salt spray resistance, and effectively enhancing the bonding strength and overall corrosion resistance. Detailed Implementation

[0020] The following embodiments provide a further detailed description of this application.

[0021] Example of preparation of zinc plating anti-corrosion solution Talc powder was purchased from Hubei Xinhongli Chemical Co., Ltd., item number XHL5139; nano silica was purchased from Hangzhou Jiupeng New Materials Co., Ltd., item number 115542.

[0022] Preparation Example 1 (1) Add 1.5g of nano zinc oxide, 1.0g of alumina powder, 0.5g of talc powder and 1.5g of nano silica to 20.0g of anhydrous ethanol, ball mill at 300rpm for 60min, and spray dry (inlet air temperature 180℃, outlet air temperature 90℃) to obtain functional particles. (2) Heat 60g zinc and 35g aluminum to 600℃, add 1g silicon, keep warm and stir for 20min, add 0.5g functional particles, continue stirring for 20min to obtain zinc anti-corrosion solution.

[0023] Preparation Example 2 (1) 1.2g of nano zinc oxide, 0.8g of alumina powder, 0.4g of talc powder and 1.0g of nano silica were added to 20.0g of anhydrous ethanol, ball-milled at 300rpm for 40min, and spray-dried (inlet air temperature 180℃, outlet air temperature 90℃) to obtain functional particles.

[0024] (2) Heat 55g zinc and 30g aluminum to 590℃, add 0.8g silicon, keep warm and stir for 15min, add 0.3g functional particles, continue stirring for 10min to obtain zinc anti-corrosion solution.

[0025] Preparation Example 3 The difference from Preparation Example 1 is that no nano-silica is added.

[0026] Preparation Example 4 The difference from Preparation Example 1 is that no talc is added.

[0027] Example of preparation of functional solution The silane coupling agent was purchased from Shaoguan Yang'an Chemical Co., Ltd., and its model number is KH-560.

[0028] Preparation Example 1 (1) Add 100g sodium citrate and 10g tannic acid to 600g water, stir well, and adjust the pH of the solution to 6.5 to obtain sodium citrate solution; (2) Add 6g of phytic acid to the sodium citrate solution obtained in step (1), stir for 10min, add 3g of silane coupling agent, and continue stirring for 20min to obtain a mixture; (3) Add 0.5g sodium molybdate, 2.0g sodium tungstate and 1.5g aminotrimethylphosphonic acid to the mixture obtained in step (2), continue stirring for 15min, let stand for 20min to obtain the functional solution.

[0029] Preparation Example 2 (1) Add 100g sodium citrate and 8g tannic acid to 600g water, stir well, and adjust the pH of the solution to 5.5 to obtain sodium citrate solution; (2) Add 4g of phytic acid to the sodium citrate solution obtained in step (1), stir for 5 minutes, add 2.5g of silane coupling agent, and continue stirring for 15 minutes to obtain a mixture; (3) Add 0.3g sodium molybdate, 1.5g sodium tungstate and 1.0g aminotrimethylphosphonic acid to the mixture obtained in step (2), continue stirring for 10min, let stand for 20min to obtain the functional solution.

[0030] Preparation Example 3 The difference from Preparation Example 1 is that tannic acid is not added in step (1).

[0031] Preparation Example 4 The difference from Preparation Example 1 is that phytic acid is not added in step (2).

[0032] Preparation Example 5 The difference from Preparation Example 1 is that aminotrimethylphosphonic acid is not added in step (2).

[0033] Preparation Example 6 The difference from Preparation Example 1 is that sodium citrate is not added in step (3). Example

[0034] In the following examples, the metal wire was purchased from Kelong Petrochemical Equipment Packing Co., Ltd. in Pingxiang City, Jiangxi Province.

[0035] Example 1: A process for corrosion protection of hot-dip galvanized wire, comprising the following steps: (1) Immerse 10g of metal wire in 200g of zinc anti-corrosion solution, galvanize at 560℃ for 60s, cool to 100℃, wash with water at 80℃ and dry at 80℃ for 1h to obtain pretreated zinc wire. (2) Immerse the pretreated zinc wire obtained in step (1) in 200g of functional solution for 5min, dry at 80℃ for 0.5h, and cool to room temperature. The zinc plating anti-corrosion solution was prepared using the method described in Example 1 of the zinc plating anti-corrosion solution preparation; the functional particles were prepared using the method described in Example 1 of the functional particle preparation.

[0036] Example 2: A process for corrosion protection of hot-dip galvanized wire, comprising the following steps: (1) Immerse 10g of metal wire in 200g of zinc anti-corrosion solution, galvanize at 550℃ for 60s, cool to 80℃, wash with water at 80℃ and dry at 80℃ for 1h to obtain pretreated zinc wire. (2) Immerse the pretreated zinc wire obtained in step (1) in 200g of functional solution for 3min, dry at 80℃ for 0.5h, and cool to room temperature. The zinc plating anti-corrosion solution was prepared using the method described in Example 2 of the zinc plating anti-corrosion solution preparation; the functional particles were prepared using the method described in Example 2 of the functional particle preparation.

[0037] Example 3: A process for corrosion protection of hot-dip galvanized wire, which differs from Example 1 in that the galvanizing anti-corrosion solution is prepared using the method in Example 3 of galvanizing anti-corrosion solution preparation.

[0038] Example 4: A process for corrosion protection of hot-dip galvanized wire, the difference from Example 1 is that the galvanizing anti-corrosion solution is prepared by the method in Example 4 of galvanizing anti-corrosion solution preparation.

[0039] Example 5: A process for corrosion protection of hot-dip galvanized wire, which differs from Example 1 in that the functional solution is prepared using the method in Functional Solution Preparation Example 3.

[0040] Example 6: A process for corrosion protection of hot-dip galvanized wire, which differs from Example 1 in that the functional solution is prepared using the method in Functional Solution Preparation Example 4.

[0041] Example 7: A process for corrosion protection of hot-dip galvanized wire, which differs from Example 1 in that the functional solution is prepared using the method in Functional Solution Preparation Example 5.

[0042] Example 8: A process for corrosion protection of hot-dip galvanized wire, which differs from Example 1 in that the functional solution is prepared using the method in Functional Solution Preparation Example 6.

[0043] Example 9: A process for corrosion protection of hot-dip galvanized wire, which differs from Example 1 in that the functional particles undergo the following pretreatment: 2g of functional particles are immersed in 100g of ethanol solution containing 10% silica sol, activated for 1 hour, filtered, and dried at 80℃ for 2 hours.

[0044] Example 10: A process for corrosion protection of hot-dip galvanized wire, which differs from Example 1 in that the functional particles undergo the following pretreatment: 2g of functional particles are immersed in 100g of ethanol solution containing 10% silica sol, activated for 0.8h, filtered, and dried at 80℃ for 2h.

[0045] Comparative Example Comparative Example 1: A process for corrosion protection of hot-dip galvanized wire, which differs from Example 1 in that no functional particles are added.

[0046] Performance testing Hot-dip galvanized wires prepared according to the methods in the examples and comparative examples were subjected to performance tests according to the following methods, and the test results are recorded in Table 1.

[0047] 1. Peel Test: Following GB / T 5270 standard, the 90° peel method was used. A 200mm long and 10mm wide sample was cut from the galvanized wire. High-strength epoxy resin was used to bond the coated surface of the sample to a stainless steel fixture. After the adhesive had fully cured, the sample was placed on a universal testing machine, and the fixture was set to peel vertically upwards at a constant speed of 5 mm / min until the coating was completely separated from the substrate. 2. Abrasion loss: The corrosion resistance of the hot-dip galvanized wire obtained in this application was tested in accordance with GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test". The test was conducted using a neutral salt spray test to simulate the marine atmospheric environment, with a NaCl solution of 50 g / L ± 5 g / L and a test period of 168 h.

[0048] Table 1. Performance test results of the hot-dip galvanized wires prepared in the examples and comparative examples. Example 1 2.2 0.21 Example 2 2.0 0.23 Example 3 1.8 0.20 Example 4 2.0 0.25 Example 5 1.4 0.50 Example 6 1.5 0.42 Example 7 1.3 0.27 Example 8 1.2 0.31 Example 9 2.8 0.11 Example 10 2.5 0.13 Comparative Example 1 0.9 0.88 As shown in Table 1, the hot-dip galvanized wires prepared in Examples 1-2 of this application have good interfacial strength and corrosion resistance. Compared with Example 1, the peel strength of Example 3 is lower, indicating that nano-silica can improve the interfacial compatibility of the particle surface and increase the interfacial strength. Compared with Example 1, the corrosion resistance of Example 4 is lower, indicating that talc can hinder the penetration of corrosive media. Compared with Example 1, the peel strength and corrosion resistance of Examples 5 and 6 are lower, which may be due to the lack of tannic acid and phytic acid, resulting in the inability to form a dual-combination system of organic chelation and inorganic crosslinking. Compared with Example 1, the peel strength and corrosion resistance of Examples 7 and 8 are lower, which may be due to the disappearance of the synergistic stabilizing effect of aminotrimethylphosphonic acid and sodium citrate. Compared with Example 1, the peel strength and corrosion resistance of Examples 9 and 10 are higher, which may be due to the modification of the functional particle surface by silica sol, increasing the interfacial strength and corrosion resistance. Compared with Example 1, Comparative Example 1 shows a significant decrease in peel strength and corrosion resistance, which may be due to the lack of functional particles.

[0049] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A process for corrosion protection of hot-dip galvanized wire, characterized in that, Includes the following steps: (1) Immerse the metal wire in the zinc anti-corrosion solution, galvanize it at 550-560℃, cool it to 80-100℃, wash and dry it to obtain pretreated zinc wire; (2) Immerse the pretreated zinc wire in the functional solution for 3-5 minutes, dry, and cool. The preparation method of the zinc plating anti-corrosion solution includes the following steps: Zinc and aluminum are heated to 590-600℃, silicon is added, and the mixture is kept warm and stirred for 15-20 minutes. Functional particles are then added, and the mixture is stirred for another 10-20 minutes to obtain a zinc-plating anti-corrosion solution.

2. The process for corrosion protection of hot-dip galvanized wire according to claim 1, characterized in that, The mass ratio of zinc, aluminum, silicon and functional particles is 55-60:30-35:0.8-1:0.3-0.

5.

3. The process for corrosion protection of hot-dip galvanized wire according to claim 1, characterized in that, The method for preparing the functional particles includes the following steps: Nano zinc oxide, aluminum oxide, talc, and nano silica were added to anhydrous ethanol, ball-milled for 40-60 minutes, and spray-dried to obtain functional particles.

4. The process for corrosion protection of hot-dip galvanized wire according to claim 3, characterized in that, The mass ratio of the nano zinc oxide, aluminum oxide, talc powder and nano silica is 1.2-1.5:0.8-1.0:0.4-0.5:1-1.

5.

5. The process for corrosion protection of hot-dip galvanized wire according to claim 1, characterized in that, The functional particles undergo the following pretreatment: Add the functional particles to an ethanol solution containing silica sol, activate for 0.8-1 hour, filter, and dry.

6. The process for corrosion protection of hot-dip galvanized wire according to claim 1, characterized in that, The method for preparing the functional solution includes the following steps: (1) Add sodium citrate and tannic acid to water, stir evenly, and adjust the pH of the solution to 5.5-6.5 to obtain sodium citrate solution; (2) Add phytic acid to sodium citrate solution, stir for 5-10 min, add silane coupling agent, and continue stirring for 15-20 min to obtain a mixture; (3) Add sodium molybdate, sodium tungstate and aminotrimethylphosphonic acid to the mixture, continue stirring for 10-15 minutes, let stand, and obtain the functional solution.

7. The process for corrosion protection of hot-dip galvanized wire according to claim 6, characterized in that, The mass ratio of sodium citrate, tannic acid, phytic acid, sodium molybdate, sodium tungstate, and aminotrimethylphosphonic acid is 100:8-10:4-6:0.3-0.5:1.5-2:1.0-1.

5.

8. A hot-dip galvanized wire anti-corrosion method, characterized in that, It is prepared by any one of the preparation methods described in claims 1-7.